Achieving Alignment in the Preparation of CSPAP Leaders in PETE Programs. Issue 2 (12th February 2017) - Bulger, Sean; Illg, Kiel; Jones, Emily
Abstract : The emergence of a research focus on comprehensive school physical activity programs (CSPAP) has prompted faculty within physical education teacher education (PETE) at West Virginia University to reconceptualize undergraduate, graduate and doctoral plans of study. In response to their experiences during the implementation of several multicomponent school-based interventions, researchers completed a web-based concept mapping process to inform PETE curriculum enhancement. The purpose of that study was to identify the knowledge, skills and behavioral competencies that a school leader would need to develop and sustain a CSPAP. Five themes emerged: (1) teambuilding and facilitating, (2) capacity building, (3) knowledge of instructional practice, (4) content knowledge, and (5) program development and management. This article describes the steps taken to introduce CSPAP at the undergraduate, graduate and doctoral levels in order to facilitate the development of related competencies in beginning and advanced teacher candidates, and to meet the needs of doctoral students intending to pursue a professional position in higher education.